ASHA-Led Community-Based Groups to Support Control of Hypertension in Rural India Are Feasible and Potentially Scalable - Riddell, Michaela A.; Mini, G. K.; Joshi, Rohina; Thrift, Amanda G.; Guggilla, Rama K.; Evans, Roger G.; Thankappan, Kavumpurathu R.; Chalmers, Kate; Chow, Clara K.; Mahal, Ajay S.; Kalyanram, Kartik; Kartik, Kamakshi; et al. (Frontiers in Medicine, 2021)
Background: To improve the control of hypertension in low- and middle-income countries, we trialed a community-based group program co-designed with local policy makers to fit within the framework of India’s health system. Trained accredited social health activists (ASHAs), delivered the program, in three economically and developmentally diverse settings in rural India. We evaluated the program’s implementation and scalability. Methods: Our mixed-methods process evaluation was guided by the United Kingdom Medical Research Council guidelines for complex interventions. Meeting attendance reports, as well as blood pressure and weight measures of attendees and adherence to meeting content and use of meeting tools were used to evaluate the implementation process. Thematic analysis of focus group discussions with participants and ASHAs as well as meeting reports and participant evaluation were used to investigate the mechanisms of impact. Results: Fifteen ASHAs led 32 community-based groups in three rural settings in the states of Kerala and Andhra Pradesh, Southern India. Overall, the fidelity of intervention delivery was high. Six meetings were delivered over a 3-month period to each of the intervention groups. Culturally appropriate intervention resources and the training of ASHAs, and supportive supervision of them during the program were critical enablers to program implementation. Conclusions: Culturally appropriate community-based group programs run by trained and supported ASHAs are a successful and scalable model for improving the control of hypertension in rural India. Trial registration: Clinical Trial Registry of India [CTRI/2016/02/006678, Registered prospectively]